WebGIS-Based Mapping of Disability-Friendly Public Facilities in Sidoarjo: Pemetaan Fasilitas Ramah Disabilitas Berbasis WebGIS di Sidoarjo - Maulana, Mahardika Rafi; Findawati, Yulian; Sumarno , Sumarno; Eviyanti, Ade (Indonesian Journal of Innovation Studies, 2023)
This research aims to develop a WebGIS platform to provide accurate information about disabled-friendly public facilities and service locations in Sidoarjo, Indonesia, using 2018 Susenas data on disability prevalence. The method involves data input by administrators and data access by users. The resulting WebGIS-based map of public facilities for persons with disabilities is accessible online. The system facilitates easy location-based access to physical accessibility facilities, infrastructure, and disability-friendly public services. The implications of this study include improved access to education, healthcare, and public facilities for individuals with disabilities in Sidoarjo, thus contributing to a more inclusive society. Highlights: Sidoarjo, Indonesia, using 2018 Susenas data on disability prevalence. Enabled easy access to accurate information about physical accessibility facilities, infrastructure, and disability-friendly public services. Improved access to education, healthcare, and public facilities for individuals with disabilities in Sidoarjo, contributing to a more inclusive society.